2003
DOI: 10.1017/s0047404503324017
|View full text |Cite
|
Sign up to set email alerts
|

The /ay/ diphthong in a Martha's Vineyard community: What can we say 40 years after Labov?

Abstract: This article revisits Labov's (1962, 1972a) germinal sociolinguistic work on Martha's Vineyard speech, providing a synchronic analysis of the /ay/ diphthong in words like right and time, and, in turn, a diachronic perspective on a sound change in progress. Labov observed that the first element of the /ay/ diphthong was raised in the speech of Martha's Vineyarders, particularly fishermen, and he correlated it with social factors like identity (i.e., local heritage) and resistance to summer visitors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 18 publications
1
24
0
1
Order By: Relevance
“…Although there had been a trend away from 0ai0 raising since Labov's study, the raised 0ai0 continued to be found in all environments on Martha's Vineyard, but it was more prominent in the environments predicted by Canadian raising. Following L. in Blake & Josey, 2003, 1 Blake and Josey favored an interpretation in which ideology shapes variation and noted that the strong division between islanders and mainlanders appeared to be weakening, a situation that freed the 0ai0 raising from its previous symbolic meaning. They further noted that an independent, ideologyfree, new change toward the more natural process of Canadian raising had taken place in Martha's Vineyard as in other areas of North America.…”
Section: E U N I T E D S T a T E Smentioning
confidence: 99%
See 1 more Smart Citation
“…Although there had been a trend away from 0ai0 raising since Labov's study, the raised 0ai0 continued to be found in all environments on Martha's Vineyard, but it was more prominent in the environments predicted by Canadian raising. Following L. in Blake & Josey, 2003, 1 Blake and Josey favored an interpretation in which ideology shapes variation and noted that the strong division between islanders and mainlanders appeared to be weakening, a situation that freed the 0ai0 raising from its previous symbolic meaning. They further noted that an independent, ideologyfree, new change toward the more natural process of Canadian raising had taken place in Martha's Vineyard as in other areas of North America.…”
Section: E U N I T E D S T a T E Smentioning
confidence: 99%
“…yard (Blake & Josey, 2003;Eckert, 2000;Milroy, 2003). It was all enough to make one nostalgic for the good old days when things were simpler, and Canadian raising was predictable and, well, Canadian.…”
mentioning
confidence: 99%
“…These men were diverging from the patterns in the uncentralized incoming dialects. Large-scale longitudinal studies, like the research conducted on Martha's Vineyard (see also Blake and Josey 2003;Pope et al 2007), are necessary to tease apart the roles of social preferences and novel perceptual input in cases of adult dialect acquisition and long-term change. However, in the shortterm, we can pit social preferences and novel perceptual input against one another in a spontaneous phonetic imitation paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…These projects, designed mainly as TREND STUDIES, in which communities that had been studied a decade or more previously were resampled, include Brink & Lund 1979, Cedergren 1988, Trudgill 1988, Thibault & Daveluy 1989, Ashby 2001, Blake & Josey 2003, and Josey 2004. A second type of longitudinal study is the PANEL STUDY, in which the same individuals are followed across time.…”
Section: Introductionmentioning
confidence: 99%